A conceptual replication of an implicit test of grammatical gender effects on inanimate concepts - Devyani Mahajan; Frank H. Durgin (Language and Cognition)
It has been argued that the incidental and arbitrary use of gender markings for inanimate concepts in language may affect the conceptualization or semantics of those inanimate concepts. The present article sought to replicate the findings of a classic paper that made this argument. Konishi used the potency dimension of the semantic differential method as an implicit measure of perceived gender. He reported that words for inanimate concepts of masculine grammatical gender were rated as higher in potency than words for the same concepts that had feminine grammatical gender. Two preregistered replication studies are reported here. The first was a conceptual replication of Konishi’s study that was conducted with 240 bilingual native speakers of either German or Spanish. Included in the study was a follow-up with 120 monolingual native English speakers. This data was used to test whether the grammatical gender in the native languages of German and Spanish speakers affected their sense of the potency of common inanimate categories when tested in a second language (English) in which they were fluent and the nouns had no grammatical gender. A second version of the study was conducted in the native languages of Spanish and German speakers, as a closer attempt at a replication of Konishi’s original study. The results of both studies provided evidence against the grammatical-gender hypothesis. Bayesian tests of both studies strongly favored the null hypothesis that there were no grammatical gender effects on implicit measures of perceived potency.